Promoting growth and morpho-physiological attributes in linseed (Linum usitatissimum L.) using indole acetic acid and gibberellic acid applied individually or jointly as foliar spray - Hussain, Khalid; Diyyal, Fatima Asghar; Nawaz, Khalid; Arshad, Noshia; Ali, Uswa; Qurban, Mohammad (International Journal of Applied and Experimental Biology, 2023)
Gibberellic acid (GA3) and indole-3-acetic acid (IAA) are commercially and scientifically important due to their promising impacts on growth, quantity and quality of most crops. The current work intended to observe the effect of foliar applications of plant growth regulators (IAA and GA3) on linseed morpho-biochemical attributes and key antioxidants. Indole-3-acetic acid showed more beneficial effects on growth and antioxidant activities than those by GA3. Root length, shoot length, photosynthetic rate, root fresh weight, and N were respectively 38%, 25%, 38%, 60%, and 1.26% higher with combined treatments of IAA+GA3 than those of the control plants at the vegetative stage. The effect of IAA was highly significant on N percentage, total protein contents and fibre percentage in linseed at both seedling and vegetative stages. Overall, the nutritional value of linseed was boosted by both PGRs, i.e., GA3 and IAA. Furthermore, it is recommended that IAA, GA3 and their combined applications can be used to enhance the quality of cereal crops.